Upaya Meningkatkan Hasil Belajar IPS Materi Permintaan Dan Penawaran Serta Harga Pasar Melalui Model Problem Based Learning Pada Siswa Kelas VIIA SMP Negeri 2 Pakis Kabupaten Magelang Tahun Pelajaran 2021/2022 - Prawata, Prawata (Faculty Of Education, 2022)
One of the problems in Learning Social Sciences (IPS) in class VII.A SMP Negeri 2 Pakis is the weak ability of students to apply knowledge to solve problems in real life, especially in understanding supply and demand as well as market prices. To overcome this problem, a Classroom Action Research (CAR) was conducted using the Problem Based Learning Model. The purpose of this study was to improve the learning outcomes of class VII A students of SMP Negeri 2 Pakis in the 2021/2022 academic year using the Problem Based Learning Model. The research subjects were 26 students of class 7A consisting of 14 men and 12 women. Sources of research data obtained from qualitative data in the form of data from observations of teacher and student activities and quantitative data in the form of test data on student learning outcomes. The results of the first cycle of research were obtained by 26 students who completed individually with an average score of 79,04. While the results of the second cycle of research experienced an increase in the average value to 84,23 or an increase of 5,57%. Based on the results of this study, learning using the Problem Based Learning learning model can improve the learning outcomes of class VII.A students of SMP Negeri 2 Pakis in the 2021/2022 academic year.